Enhanced capture of waste and diluted CO2 by N/O-rich multilayered ultramicropores bio-carbon composites materials. (December 2021) - Hui, Wei; Mao, Fei-Feng; Wang, Xiang; Xu, Xin-Yi; Wang, Hai-Jun
Abstract: The effective capture of waste and diluted CO2 by porous carbon materials is extremely challenging. Herein, a facile one-step strategy was developed to prepare activated N/O-rich multilayer ultramicropores carbon composite materials for capturing waste and diluted CO2 effectively by directly carbonizing urea and d -glucose with a novel non-corrosive and non-toxic chemical activator of potassium acetate. Especially, the diluted CO2 adsorptive capacity of the porous carbon material reached 1.38 mmol/g and 0.57 mmol/g at 0.15 bar and 0.05 bar (0 °C) respectively. Meanwhile, the retention time up to 85 min in the diluted CO2 breakthrough experiment further confirms the outstanding adsorptive property of the materials, implying their potential for CO2 /N2 separation in the industrial field. Graphical abstract: Image 1 Highlights: Preparation of N/O-rich multilayered ultramicropores bio-carbon by the one-step method. The synergistic effect of double heteroatoms enhances the efficacy of diluted CO2 capture capacity. PGNC-0.5 has the highest capacity for extremely diluted CO2 uptake. PGNC-0.5 adsorbent obtained an effective retention time of up to 85 min in the breakthrough experiment of extremely diluted CO2 .